Imaging‐based biomarkers: Changes in the tumor interface of pancreatic ductal adenocarcinoma on computed tomography scans indicate response to cytotoxic therapy. Issue 8 (25th January 2018) - Amer, Ahmed M.; Zaid, Mohamed; Chaudhury, Baishali; Elganainy, Dalia; Lee, Yeonju; Wilke, Christopher T.; Cloyd, Jordan; Wang, Huamin; Maitra, Anirban; Wolff, Robert A.; Varadhachary, Gauri; Overman, Michael J.; et al.
Abstract : BACKGROUND: The assessment of pancreatic ductal adenocarcinoma (PDAC) response to therapy remains challenging. The objective of this study was to investigate whether changes in the tumor/parenchyma interface are associated with response. METHODS: Computed tomography (CT) scans before and after therapy were reviewed in 4 cohorts: cohort 1 (99 patients with stage I/II PDAC who received neoadjuvant chemoradiation and surgery); cohort 2 (86 patients with stage IV PDAC who received chemotherapy), cohort 3 (94 patients with stage I/II PDAC who received protocol‐based neoadjuvant gemcitabine chemoradiation), and cohort 4 (47 patients with stage I/II PDAC who received neoadjuvant chemoradiation and were prospectively followed in a registry). The tumor/parenchyma interface was visually classified as either a type I response (the interface remained or became well defined) or a type II response (the interface became poorly defined) after therapy. Consensus (cohorts 1‐3) and individual (cohort 4) visual scoring was performed. Changes in enhancement at the interface were quantified using a proprietary platform. RESULTS: In cohort 1, type I responders had a greater probability of achieving a complete or near‐complete pathologic response (21% vs 0%; P = .01). For cohorts 1, 2, and 3, type I responders had significantly longer disease‐free and overall survival, independent of traditional covariates of outcomes and of baseline and normalized cancer antigen 19‐9 levels. In cohort 4, 2 senior radiologists achieved a κ value of 0.8, and the interface score was associated with overall survival. The quantitative method revealed high specificity and sensitivity in classifying patients as type I or type II responders (with an area under the receiver operating curve of 0.92 in cohort 1, 0.96 in cohort 2, and 0.89 in cohort 3). CONCLUSIONS: Changes at the PDAC/parenchyma interface may serve as an early predictor of response to therapy. Cancer 2018;124:1701‐9 . © 2018 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial‐NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non‐commercial and no modifications or adaptations are made. Abstract : An imaging feature of pancreatic cancer is identified that indicates a response to cytotoxic therapies. This may be helpful as an early predictor of response for clinical trials and for deciding whether to change therapy.